Differential inflammatory responses to acute exercise and ex vivo immune challenge in young and master athletes - Minuzzi, Luciele Guerra; De Souza Teixeira, Alexandre Abilio; Figueiredo, Caique; Dorneles, Gilson; Branco, Anna Cláudia Castelo; Silva, Bruna Spolador de Alencar; Valenzuela, Pedro L.; Peres, Alessandra; Lucia, Alejandro; Sato, Maria Notomi; Rosa Neto, José Cesar; Krüger, Karsten; et al. (Frontiers in Immunology, 2025)
BackgroundLifelong exercise is associated with beneficial immune adaptations, but the extent to which these adaptations manifest during an acute inflammatory challenge remains unclear. Therefore, we aimed to compare the inflammatory responses to ex vivo whole blood and peripheral blood mononuclear cells [PBMCs] cultures from young and master athletes, before and after a single bout of moderate-intensity exercise.MethodsYoung (n=7; 22 ± 4 years) and master (n=12; 52 ± 9 years) female and male athletes with similar performance levels performed a 30-minute bout of moderate-intensity exercise. Blood samples were collected before and post-exercise to assess cytokine production in whole blood and PBMCs after stimulation with lipopolysaccharide [LPS] and a cocktail with phorbol 12-myristate 13-acetate [PMA] plus ionomycin.ResultsIn whole blood, LPS induced higher interleukin [IL]-6 release in both groups, with a greater increase in young athletes at post-exercise (p=0.014). Tumor necrosis factor [TNF]-α levels increased only in young athletes (p<0.0001). In PBMCs, master athletes showed lower LPS-induced TNF-α release, increasing only post-exercise (p<0.034), whereas young athletes responded at both baseline (p<0.001) and post-exercise (p=0.003). Under PMA/ionomycin stimulation, TNF-α (p<0.0001) and interferon (IFN)-γ (p=0.007) release increased only in young athletes, while IL-6 production decreased in young athletes at baseline (p=0.002) and post-exercise (p=0.003).ConclusionYoung athletes exhibit a stronger cytokine response to ex vivo inflammatory stimuli, while master athletes demonstrate a more controlled and regulated inflammatory profile.